2017
DOI: 10.3390/molecules22030410
|View full text |Cite
|
Sign up to set email alerts
|

DL0410 Ameliorates Memory and Cognitive Impairments Induced by Scopolamine via Increasing Cholinergic Neurotransmission in Mice

Abstract: Deficiency of the cholinergic system is thought to play a vital role in cognitive impairment of dementia. DL0410 was discovered as a dual inhibitor of acetylcholinesterase (AChE) and butyrylcholinestease (BuChE), with potent efficiency in in-vitro experiments, but its in vivo effect on the cholinergic model has not been evaluated, and its action mechanism has also not been illustrated. In the present study, the capability of DL0410 in ameliorating the amnesia induced by scopolamine was investigated, and its ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 48 publications
(57 reference statements)
3
24
0
Order By: Relevance
“…Our previous studies affirmed the efficacy and safety of DL0410 [ 18 , 19 , 20 , 21 ]. It was observable that DL0410 had the ability to enhance deficits of memory in scopolamine-induced amnesia in mice by increasing the ACh level in a dose-dependent manner [ 20 ]. In addition, DL0410 had an effect on the reduction of Aβ plaques.…”
Section: Introductionsupporting
confidence: 78%
“…Our previous studies affirmed the efficacy and safety of DL0410 [ 18 , 19 , 20 , 21 ]. It was observable that DL0410 had the ability to enhance deficits of memory in scopolamine-induced amnesia in mice by increasing the ACh level in a dose-dependent manner [ 20 ]. In addition, DL0410 had an effect on the reduction of Aβ plaques.…”
Section: Introductionsupporting
confidence: 78%
“…In addition, based on the studies reporting the potent acetylcholinesterase inhibitory effect of galangin, it was suggested that galangin might be a potential treatment option in Alzheimer's disease and other dementias (17,23,26,27). Low brain acetylcholine concentrations, especially in the hippocampus, are associated with cognitive dysfunction and increasing acetylcholine concentrations in the brain via inhibition of acetylcholinesterase, which is accepted as a helpful way of treating the cognitive dysfunction seen in Alzheimer's disease and other dementias (28,29). In this study, galangin prevented the memory impairment induced by scopolamine or mecamylamine.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that BSYZ could improve the learning and memory of SAMP8 mice, which is according with our previous studies [ 9 , 10 ]. Donepezil (DON) showed the similar effect on elevating the availability of ACh in the brain, which has been documented as critical for the effective management of Alzheimer's disease and used as a positive control in ameliorating memory and cognitive impairments [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%